Optimising asthma inhaler prescribing to improve health outcomes and lower greenhouse gas emissions - Ali Rajani; Monika Bhardva; Siva Mahendran; Lola Lowenthal; Natasha Nwosu; Sam Maisey (Future Healthcare Journal)
Introduction: The UK has the worst mortality rate for asthma among its European counterparts.1 Asthma presentations to the emergency department (ED) provide an opportunity to resolve the immediate flare, assess for exacerbating factors and prescribe appropriate inhaler therapy to reduce airway remodelling. Sustainable inhaler prescribing aims to: (1) improve asthma control at the point of discharge; and (2) minimise prescription of high greenhouse gas (GHG) propellants in pressure metered dose inhalers (pMDI). Materials and methods: This was a retrospective observational study on the efficacy of inhalers prescribed on discharge following treatment of asthma or unspecified shortness of breath at a southwest London district general hospital ED over a 3-month period, with review of the environmental impact caused by pMDI therapy.Inclusion criteria: 1. Discharged from ED within 24 h of arrival; 2. Diagnosed ‘asthma’ or an unspecified ‘wheeze’ on the discharge summary or clerking note; 3. Prescribed a ‘to-take out’ (TTO) prescription of salbutamol and/or clenil (beclomethasone) pMDI; 4. TTO issued from on-site Boots pharmacy.Exclusion criteria: 1. Age <16 years old; 2. Diagnosed with ‘COPD’ on the final discharge summary or clerking note; 3. TTO issued from the pre-pack supply available in ED (unregulated supply). Results and discussion: 65 patients met the inclusion criteria, most of whom were female (61.5%). 30 patients (46.2%) were identified as having an asthma exacerbation, and the remainder with wheeze due to ‘other’ causes (eg, ‘LRTI with bronchospasm’).78.5% of patients were prescribed a salbutamol pMDI, 3.1% were prescribed a beclomethasone pMDI and 9.2% were prescribed a combination of both inhalers. 70.8% of patients were also prescribed oral prednisolone as a TTO.On average, there was a time delay of 11 h and 35 min between prescription and issue of inhalers at the on-site pharmacy.Only 9.2% of patients were offered respiratory follow-up. Unfortunately, 18.5% of patients re-presented to the ED with acute airways symptoms within 90 days. Of these patients, half initially presented with an asthma exacerbation.The cumulative cost of inhalers in this study was £260.The first-line treatment for asthma as per joint British Thoracic Society (BTS)/NICE/ Scottish Intercollegiate Guidelines Network (SIGN) guidance is inhaled low-dose ICS/formoterol, used in an anti-inflammatory reliever (AIR) or maintainer and reliever therapy (MART) regimen as appropriate.2 Even those on appropriate inhaler therapy were prescribed salbutamol ± beclomethasone pMDI erroneously. This resulted in a high re-presentation rate to secondary care, indicating poor disease control.All the inhalers prescribed in this study used HFA-134 propellants, with a cumulative GHG burden of 804 kg CO2e, equivalent to driving a petrol car for 3,048 miles (think London to Moscow).3 Conclusion: Asthma is poorly managed at the point of discharge. Our proposed solutions are: 1. To add a Symbicort turbohaler to the ED cupboard to improve symptom management, reduce GHG burden and time to TTO; 2. To update local emergency care guidelines to reflect best practice; 3. Provide patients with a self-management pack.We will implement these changes as a local quality improvement project. 1. Causes of death - standardised death rate by region of residence, 2011–2018. https://ec.europa.eu/eurostat/databrowser/view/HLTH_CD_ASDR2__custom_2053067/default/table?lang=en [Accessed 7 June 2025]. 2. Principles of pharmacological treatment, 2020. www.nice.org.uk/guidance/ng245/chapter/Recommendations#principles-of-pharmacological-treatment [Accessed 7 June 2025]. 3. Greenhouse gas reporting: conversion factors, 2023. www.gov.uk/government/publications/greenhouse-gas-reporting-conversion-factors-2023 [Accessed 7 June 2025].